Certain peculiarities about the apprehension of the works of fiction among students of technical and humanitarian sciences - Barzdžiukienė, Leonora (Knygotyra, 1981)
The article analyses the problem of apprehension of fiction in terms of theory as well as presents the results of the concrete sociological investigation having been carried out in December 1977 — April 1918 among the students of Kaunas Antanas Sniečkus Politechnic Institute and Vilnius Vincas Mickevičius Kapsukas State University on the basis of questionnaire tests “The Writer and the Reader”, “My point of view on poetry”. The article also analyses the specific character of artistic apprehension of 2 short stories and 4 poems, depending on the type of studies and other faktors: the intensity and culture of reading, the student advancement, the standpoint on the values given by the works of fiction.